Effect of cardiopulmonary bypass on the pharmacokinetics of propranolol and atenolol - Carmona,M.J.C. (2009)
The pharmacokinetics of some β-blockers are altered by cardiopulmonary bypass (CPB). The objective of this study was to compare the effect of coronary artery bypass graft (CABG) surgery employing CPB on the pharmacokinetics of propranolol and atenolol. We studied patients receiving oral propranolol with doses ranging from 80 to 240 mg (N = 11) or atenolol with doses ranging from 25 to 100 mg (N = 8) in the pre- and postoperative period of CABG with moderately hypothermic CPB (32°C). On the day before and on the first day after surgery, blood samples were collected before β-blocker administration and every 2 h thereafter. Plasma levels were determined using high-performance liquid chromatography and data were treated by pharmacokinetics-modelling. Statistical analysis was performed using ANOVA or the Friedman test, as appropriate, and P < 0.05 was considered to be significant. A prolongation of propranolol biological half-life from 5.41 ± 0.75 to 11.46 ± 1.66 h (P = 0.0028) and an increase in propranolol volume of distribution from 8.70 ± 2.83 to 19.33 ± 6.52 L/kg (P = 0.0032) were observed after CABG with CPB. No significant changes were observed in either atenolol biological half-life (from 11.20 ± 1.60 to 11.44 ± 2.89 h) or atenolol volume of distribution (from 2.90 ± 0.36 to 3.83 ± 0.72 L/kg). Total clearance was not changed by surgery. These CPB-induced alterations in propranolol pharmacokinetics may promote unexpected long-lasting effects in the postoperative period while the effects of atenolol were not modified by CPB surgery.